Assessing Factors Affecting Living Standards of Ethnic Minorities in Vietnam - Ngoc Anh, Le; Ngan, Nguyen Thu (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 1 No 3, 2021)
The authors investigate factors affecting living standards of ethnic minorities in Vietnam by using the Household Living Standards Survey 2018 dataset (VHLSS) and model regression. It is found that income has the strongest influence on living standards of ethnic minorities, while health insurance has an opposite effect. This finding provides the basis for the research team to make a number of recommendations and solutions for stakeholders to ensure and improve living standards of ethnic minorities in Vietnam.